A unified strength model for chemically toughened high-performance asphalt mixtures in ultra-thin overlay applications - Huang, Bin; Liu, Bowen; Xiao, Ge; Jin, Xin; Liu, Duyang; Liu, Jinguo; Liu, Chenxi; Ling, Yumeng; Wang, Dikuan; Xia, Chengdong (Frontiers in Materials, 2025)
To enhance the mechanical performance of ultra-thin asphalt overlays subjected to heavy traffic and severe environmental conditions, this study developed a high-performance SMA-8 asphalt mixture incorporating a chemically toughened modified binder specifically designed for ultra-thin applications. The mixture’s strength response to varying loading rates was systematically assessed through direct tensile, indirect tensile, and unconfined compressive tests, facilitating the analysis of rate-dependent behavior and strength evolution under different stress states. The results demonstrated that all strength indices increased with loading rate following power-law trends, with indirect tensile strength showing the highest sensitivity to loading rate and compressive strength exhibiting the greatest absolute magnitude. Cohesion, determined using Mohr–Coulomb analysis, increased significantly with loading rate, while the internal friction angle exhibited a non-monotonic variation, indicating complex interfacial failure mechanisms. A unified strength model was developed by normalizing and converting results across the three loading modes, providing a generalized framework for strength characterization of ultra-thin overlays. These findings offer both theoretical insights and practical guidance for the design, evaluation, and engineering application of chemically modified high-performance ultra-thin asphalt overlays.